EVALUASI KETEPATAN PENGGUNAAN OBAT PASIEN IBU HAMIL DI DEPARTEMEN OBSTETRI DAN GINEKOLOGI RUMAH SAKIT “X” - Abdushshofi, Muhammad Fikri; Elvina, Ridha; Hersunaryati, Yetti (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
In the period of pregnancy, a woman requires drug therapy due to the disturbance suffered, whether related or unrelated to the pregnancy process. Drugs taken by pregnants is noteworthy, because the drug is taken can affect the fetus. This study aimes to evaluate the accuracy of the indication, patient, and doses of drug use in pregnants in accordance with the guidelines used. The type of research is descriptive, data collection is do retrospectively. Sampling was done by purposive sampling in pregnants from the medical records of the Obstetric and Gynecology Department “X” Hospital Jakarta period from January to December, 2014. The results showed that meets the appropriate category indication as much as 99.30% and the category is not appropriate indication as much as 0.70%. Meets the appropriate category of patients as much as 99.30% and the category is not appropriate patients as much as 0.70%. Whereas, meet the appropriate category doses as much as 98.60% and the category is not appropriate doses of as much as 1.40%.